TAVR: Imaging Spectrum of Complications. Issue 6 (November 2015) - Singh, Satinder P.; Alli, Oluseun; Melby, Spencer; Lessar, Massoud; Sasse, Mark; Booker, Julian; Davies, James
Abstract : Transcatheter aortic valve replacement has recently become a suitable alternative for senile aortic stenosis in patients not suitable for surgery. With growing operative experience, appropriate patient selection, advances in imaging evaluation, and technical refinements, the outcomes have improved. Despite its less invasive nature, a unique set of complications and events are encountered during the transcatheter aortic valve replacement procedure and in the postoperative period. Knowledge of these complications, their prompt detection, and quick adequate treatment are critical in reducing the mortality and morbidity.